Effect of (Nd, Ni) co-doped on the multiferroic and photocatalytic properties of BiFeO3. (December 2015) - Vanga, Pradeep Reddy; Mangalaraja, R.V.; Ashok, M.
Graphical abstract: Highlights: Sol–gel synthesis. Saturation magnetization and ferroelectricity increases in Ni co-doped samples. Conduction mechanism is different in Nd doped and (Nd, Ni) co-doped samples. Samples show good photocatalytic activity in the presence of H2 O2 . Abstract: Bi0.95 Nd0.05 Fe1− x Ni x O3 ( x = 0, 0.01, 0.03 and 0.05) samples are synthesized by solgel method. The phase and crystal structure of the samples are confirmed by X-ray diffraction studies, Rietveld refinement is performed to calculate the structural parameters. The reflectance spectra show bands in UV and visible region and the optical band gap is calculated using Kulbeka–Munk function. The magnetization and leakage current density are strongly influenced by doping. Different conduction mechanisms are observed in Nd doped and Ni co-doped samples. All the samples exhibit ferroelectric nature at various frequencies. Photocatalytic activities of the samples are determined by the degradation of methylene blue dye in the presence of visible light and H2 O2 which shows samples are good photo-Fenton like catalyst.